2021
DOI: 10.3390/antiox10081316
|View full text |Cite
|
Sign up to set email alerts
|

The Alteration of Chloride Homeostasis/GABAergic Signaling in Brain Disorders: Could Oxidative Stress Play a Role?

Abstract: In neuronal precursors and immature neurons, the depolarizing (excitatory) effect of γ-Aminobutyric acid (GABA) signaling is associated with elevated [Cl−]i; as brain cells mature, a developmental switch occurs, leading to the decrease of [Cl−]i and to the hyperpolarizing (inhibitory) effect of GABAergic signaling. [Cl−]i is controlled by two chloride co-transporters: NKCC1, which causes Cl− to accumulate into the cells, and KCC2, which extrudes it. The ontogenetic upregulation of the latter determines the abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 156 publications
(180 reference statements)
0
13
0
Order By: Relevance
“…A very rich literature supports the notion that oxidative stress occurs in ASD as well as in several, if not all, brain diseases and disorders [ 187 ]. Sources of oxidative stress are manifold and include inflammation, gut dysbiosis, xenobiotic and drug metabolism, maternal alcohol abuse, dysfunctional mitochondria.…”
Section: Lessons From Biological Research and Suggestions For Clinica...mentioning
confidence: 94%
See 2 more Smart Citations
“…A very rich literature supports the notion that oxidative stress occurs in ASD as well as in several, if not all, brain diseases and disorders [ 187 ]. Sources of oxidative stress are manifold and include inflammation, gut dysbiosis, xenobiotic and drug metabolism, maternal alcohol abuse, dysfunctional mitochondria.…”
Section: Lessons From Biological Research and Suggestions For Clinica...mentioning
confidence: 94%
“…Following the hypothesis that oxidative stress represents a hallmark of metabolic abnormalities in several brain disorders and given that it influences a wide array of molecular pathways, the possible impact of this imbalance was studied in relation to the impairment of chloride homeostasis occurring in the GABAergic system in CNS [ 187 ]. This study showed evidence linking the impairment of intracellular chloride concentration with the occurrence of oxidative stress and inflammation in patients with different neurological and neurodevelopmental diseases, such as ASD, epilepsy, schizophrenia, Down’s Syndrome [ 187 ]. Moreover, it showed that increased oxidative stress interferes with the shift of GABAergic transmission from excitation to inhibition, a fundamental ontogenetic process under epigenetic control [ 188 ].…”
Section: The Web Of Metabolic Immunologic and Microbiologic Imbalance...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the recorded grey matter changes in schizophrenia occurs in the immediate post-onset phase [ 24 , 109 , 110 ], coinciding with the critical period of intracortical myelination [ 111 , 112 , 113 ]. Intracortical myelin mostly insulates parvalbumin containing interneurons [ 114 ] that are highly susceptible to developmental factors influencing redox balance [ 115 ] as well as GSH deficit and associated glutamate-mediated excitotoxicity [ 30 , 116 ]. In a subsample of patients reported by Pan and colleagues [ 73 ], we obtained quantitative intracortical myelin measurement and noted several regions where patients had lower intracortical myelin in the presence of higher glutamate, only when GSH levels were lower than the median (bilateral dorsolateral prefrontal cortex, right superior temporal, and left precentral gyrus and right subgenual ACC).…”
Section: Consequences Of the Putative Intracortical Gsh Deficitmentioning
confidence: 99%
“…Hypomagnesemia, postulated in migraine, was shown to enhance glutamatergic neurotransmission, leading to increased oxidative stress [ 46 ]. It is worth mentioning that neurodevelopmental disorders, including Down’s syndrome, autism spectrum disorder, schizophrenia and epilepsy, were associated with oxidative stress-induced dysregulation of chloride ion homeostasis, which is related to γ-aminobutyric acid (GABA) signaling [ 47 ]. Interestingly, oxidative stress is also supposed to be involved in the course of bipolar disorder (BP).…”
Section: The Redox Balance In Brain Disordersmentioning
confidence: 99%